Fasilitas Aplikasi Pendidikan dan Suasana Akademik Dapat Menciptakan Kepuasan dan Dampaknya Terhadap Word of Mouth Mahasiswa - Wisnalmawati Wisnalmawati; Wahyu Handayani; Olinda da Conceicao (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
The importance of building word of mouth as an efficient promotion in universities. The purpose of this study is the Educational application facilities and academic atmosphere influence word of mouth promotion, satisfaction as a mediating variable. The research approach used quantitative. The population of this study were all Master of Management students, the sample was a portion of Master of Management students, the sampling technique used purposive sampling with respondents from four universities in Indonesia. The analysis technique used is the Structural Equational Model (SEM) with the PLS Program. The results showed that 1. Application facilities and academic atmosphere did not affect word of mouth. 2. Application facilities and academic atmosphere influence word of mouth promotion which is mediated by student satisfaction. The novelty of this research is to create student satisfaction so that it can increase word of mouth. The results of this study contribute to the development of models of consumer behavior. For the University, improving the learning application training facilities will make it easier to store soft data for accreditation and accelerate the graduation of quality students so as to create satisfaction that has a positive impact by word of mouth.